2007
DOI: 10.1007/s10461-007-9348-y
|View full text |Cite
|
Sign up to set email alerts
|

New Populations at High Risk of HIV/STIs in Low-income, Urban Coastal Peru

Abstract: The HIV epidemic in Peru is concentrated primarily among men who have sex with men. HIV interventions have focused exclusively on a narrowly defined group of MSM and FSW to the exclusion of other populations potentially at increased risk. Interventions targeting MSM and FSW are insufficient and there is evidence that focusing prevention efforts solely on these populations may ignore others that do not fall directly into these categories. This paper describes nontraditional, vulnerable populations within low-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
(25 reference statements)
1
32
0
1
Order By: Relevance
“…Our findings of the high baseline prevalence and incidence rates of the STIs measured are supported by previous high prevalence findings in other studies 4,5,23,24 . This provides further validation of Lima’s lower-income MSM and TW as populations at the heart of a concentrated and active HIV epidemic and at high-risk for other STIs.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of the high baseline prevalence and incidence rates of the STIs measured are supported by previous high prevalence findings in other studies 4,5,23,24 . This provides further validation of Lima’s lower-income MSM and TW as populations at the heart of a concentrated and active HIV epidemic and at high-risk for other STIs.…”
Section: Discussionsupporting
confidence: 91%
“…Poverty and socioeconomic marginalisation of MSM leads many to engage in compensated sex for economic survival 30. A high baseline prevalence of STIs heightens the risk for the continued spread of HIV and STIs in the community 31. Deficiencies in public health resources limit access to diagnosis, treatment and public health services (such as third-party partner notification and expedited partner treatment) that could reduce the spread of HIV and other STIs in the population 32.…”
Section: Discussionmentioning
confidence: 99%
“…Other Peruvian studies have shown that people who use substances before sex are at particularly high risk of either having sex with another man, having unprotected sex with a casual partner, or having had an STD [16][17][18]. Similarly, heavy drinking significantly increases the risk of having multiple sexual partners, having had sex with a casual partner in the last year, and acquiring an STD [14,19,20].…”
Section: Overview Of Alcohol-illicit Drug Use and Associated Risky Bementioning
confidence: 96%